Hindu Medical Astrology: Basics, cases, and literature review - Prasanna R Deshpande (Wolters Kluwer Medknow Publications, 2023)
Objectives: The objectives of this study were to know the basic aspects of Hindu/Indian Medical Astrology (HMA/IMA), to discuss a few cases, and to conduct literature review on HMA. Data Source: Books, a few patients, and recent research articles. Review Methods: Articles were searched from Google Scholar, PubMed, references, and citations. Conclusion: HMA does have the potential to forecast the health of an individual. There is a pressing need to explore this area for research.